Common Best Proximity Points for Weakly Proximal Increasing Mappings: Va Pragadeeswarar - Team, Support (Thai Journal of Mathematics, 2019)
The aim of this paper is to present the existence and uniqueness of common best proximity point for weakly proximal increasing mappings satisfying certain contractive condition in a complete ordered metric spaces. Moreover, we furnish suitable examples to demonstrate the validity of the main results.